Comparative Study of Error Performance in Modulation Schemes for VLC Systems (International Journal of Engineering and Computer Science, 2015)
— Wireless communication technology is emerging very fast with reliable communication lead to emergence of verynumerous technologies. There are various modulation schemes suitable in optical wireless communication like OOK, PPM, DPIM, DHPIM,and OFDM. As modulation techniques is categorized into bandwidth & power efficient but for error performance there are fewassumptions where there is no bandwidth limitation. In this paper we analyze the error rate in AWGN channel for these modulationtechniques & the combined result shows that DPIM, DH-PIM & OFDM are applicable for future applications.